Chapter 9. Crypto staking from the Shariah perspective - Habib, Farukh (Islamic finance in the digital age, 2024)
Proof of Stake (PoS) is a consensus methodology for blockchain platforms, proposed as an alternative to Proof of Work (PoW) mechanisms. Its primary objective is to validate transactions and ascertain the truthfulness of on-chain data. Users who stake their funds receive incentives in the form of newly minted cryptoassets or transaction fees, making staking a prevalent investment activity in the cryptocurrency domain. However, for users adhering to the Islamic faith, staking introduces a distinctive challenge, particularly concerning its alignment with halal principles. This area represents a significant research gap, with shariah scholars actively engaging in the assessment of this phenomenon from a fiqh perspective. A thorough understanding of the relevant fiqh principles and rulings, in conjunction with the technical and operational facets of staking, is imperative. This chapter delineates two forms of staking: (1) staking on a Proof of Stake (PoS) blockchain, and (2) staking as the act of locking funds in a smart contract for a designated purpose. Subsequently, it explores the shariah compliance of both types.